2016
DOI: 10.5558/tfc2016-084
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and seasonal variations in soil CO2 production in a 55-year-old oriental arborvitae (Platycladus orientalis) plantation in China

Abstract: The aim of this work was to explore the vertical and seasonal variations of CO 2 within the soil profile based on Fick's law of diffusion in an oriental arborvitae plantation. We continuously measured the soil CO 2 concentration profile using CO 2 sensors buried at different depths in a coniferous forest in northern China and calculated the CO 2 flux based on the profile measurements using a dynamic model. The diurnal pattern of CO 2 concentration and flux fluctuated during the day and varied less at night. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Klimanek and Greilick (1981) found CO 2 concentrations in soil air of up to 2.9% in field experiments while examining the influence of bulk density on soil aeration for the same soil (a Chernozem at Bad Lauchstädt). A large number of field studies and field experiments have reported similar concentration ranges with maxima in the range of 1 to 5% (e.g., Pumpanen et al, 2003a, 2003b; Doff Sotta et al, 2004; Riveros‐Iregui et al, 2007; DeSutter et al, 2008; Koehler et al, 2010; Ek and Godissart, 2014; Han et al, 2014; Roland et al, 2015; Fan et al, 2016). Others have observed soil respiration processes at CO 2 concentrations below 1% (Risk et al, 2002; Jochheim et al, 2018), while concentrations of up to 10% have also been reported (Oh et al, 2005; Taneva et al, 2006; Bekele et al, 2007; Jaakkola and Simojoki, 2008; Wiaux et al, 2015).…”
Section: Resultsmentioning
confidence: 90%
“…Klimanek and Greilick (1981) found CO 2 concentrations in soil air of up to 2.9% in field experiments while examining the influence of bulk density on soil aeration for the same soil (a Chernozem at Bad Lauchstädt). A large number of field studies and field experiments have reported similar concentration ranges with maxima in the range of 1 to 5% (e.g., Pumpanen et al, 2003a, 2003b; Doff Sotta et al, 2004; Riveros‐Iregui et al, 2007; DeSutter et al, 2008; Koehler et al, 2010; Ek and Godissart, 2014; Han et al, 2014; Roland et al, 2015; Fan et al, 2016). Others have observed soil respiration processes at CO 2 concentrations below 1% (Risk et al, 2002; Jochheim et al, 2018), while concentrations of up to 10% have also been reported (Oh et al, 2005; Taneva et al, 2006; Bekele et al, 2007; Jaakkola and Simojoki, 2008; Wiaux et al, 2015).…”
Section: Resultsmentioning
confidence: 90%